PERAN STRATEGI KOMUNIKASI PEMASARAN â€œWORD OF MOUTHâ€ DALAM PENGAMBILAN KEPUTUSAN KONSUMEN - Nugraheni, Dewi Shanti (FE Program Studi Manajemen, 2008)
A company needs to communicate its products to the community in order to socialize its products so they will consume them. One of the strategy is using marketing mix which is called word of mouth which will trigger the consumers to talk and promote furthermore they will recommend its products to another consumers. In order that word of mouth as communication marketing mix strategy can take part in consumers making decision so the company must provide the satisfaction toward its consumers for the establishment of positive word of mouth. Key words: Marketing communication, word of mouth, consumers decision